CO in the C1 globule of the Helix nebula with ALMA. Issue 1 (30th October 2019) - Andriantsaralaza, M; Zijlstra, A; Avison, A
ABSTRACT: We present and analyse 12 CO, 13 CO, and C 18 O(2–1) ALMA observations of the C1 globule inside the Helix nebula in order to determine its physical properties. Our findings confirm the molecular nature of the globule with a multipeak structure. The 12 CO line has a high optical depth τ ∼10. The derived 12 C/ 13 C∼10 and 16 O/ 18 O∼115 ratios are not in agreement with the expected isotopic ratios of carbon-rich AGB stars. Assuming that the 12 CO optical depth has been underestimated, we can find a consistent fit for an initial mass of 2 M⊙ . We obtain a molecular mass of 2 × 10^-4 M_ for the C1 globule, which is much higher than its mass in the literature. Clumping could play a role in the high molecular mass of the knot. The origin of the tail is discussed. Our findings show that the most probable model appears to be shadowing. The kinematics and molecular morphology of the knot are not consistent with a wind-swept model and the photoevaporation model alone is not enough to explain the nature of the globule. We propose an integrated model where the effects of the photoevaporation, the stream, and shadowing models are all considered in the tail shaping process.